The plague of doves - Erdrich, Louise (HarperCollins, 2008)
The unsolved murder of a farm family haunts the small, white, off-reservation town of Pluto, North Dakota. The vengeance exacted for this crime and the subsequent distortions of truth transform the lives of Ojibwe living on the nearby reservation and shape the passions of both communities for the next generation.